Evaluasi Aktivitas Antibakteri Minyak Jintan Hitam Terhadap Bakteri Gram-Positif dan Gram-Negatif: Studi pada Staphylococcus aureus dan Pseudomunas aeruginosa - Salsabila, Maisan Khoiri; Rukaya, Benazir Evita; Syuhada, Syuhada (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate the antibacterial activity of black cumin oil (Nigella sativa) against Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa) bacteria. Methods: The antibacterial activity was tested using the well diffusion method with varying concentrations of black cumin oil (0.1%, 0.5%, 1%, and 2%), along with a negative control using ethyl acetate as the solvent. Additionally, a simple phytochemical screening was conducted using a test tube reaction method to detect the presence of active compounds such as alkaloids, flavonoids, tannins, and saponins. The results showed that (1) black cumin oil at a concentration of 2% produced the largest inhibition zones, measuring 15.33 Â± 3.21 mm for Staphylococcus aureus and 9.37 Â± 1.98 mm for Pseudomonas aeruginosa; (2) Statistical analysis confirmed significant differences in several treatments, with a p-value < 0.05. The antibacterial effect of black cumin oil was stronger against Gram-positive bacteria than Gram-negative bacteria, likely due to differences in bacterial cell wall structures; (3) Furthermore, black cumin oil tested positive for alkaloids and saponins, which are known as potential antimicrobial compounds. Overall, this study indicates that black cumin oil has the potential to serve as an effective natural antibacterial agent, particularly against Gram-positive Staphylococcus aureus.